О локализации средних Бохнера - Риса в классах С. М. Никольского - Грона, В.Л. (Український математичний журнал, 1993)
The conditions are investigated for localization of the Bokhner - Riesz averages in the Nikol'skii classes uαp for p∈[1,2].